Bertha Takes A Drive - Jan Adkins (Watertown, United States Charlesbridge Publishing,U.S., 2017)
In this nonfiction joyride, Bertha Benz and her sons drive across Germany in the world's first automobile. It's 1888 and Bertha Benz's husband, Karl, has invented the prototype Benz motorwagen. But the German government declares the vehicle illegal, and the church calls it the devil's work. Unbeknownst to her husband, Bertha steals away with her two sons and drives nearly one hundred miles to prove just how amazing the motorwagen is. Bertha's mechanical savvy gets the boys to Grandma's house safely, and the remarkable mother/son road trip reduces global concern about moving vehicles.
Keywords: Circle Time